AN IMPROVEMENT OF THE RISK MANAGEMENT SYSTEM FOR THE PREVENTION OF OCCUPATIONAL DISEASES - V. A. Kaptsov; V. B. Pankova (Сеченовский вестник, 2012)
This entry deals with the problem of improvement of the risk management system for prevention of occupational diseases.